Further evidence of the developmental origins of osteoarthritis: results from the Hertfordshire Cohort Study. (22nd August 2014) - Clynes, M. A.; Parsons, C.; Edwards, M. H.; Jameson, K. A.; Harvey, N. C.; Aihie Sayer, A.; Cooper, C.; Dennison, E. M.
<x content-type="archive" xml:space="preserve">Abstract</x> Investigators have suggested a link between birth weight and both hand and lumbar spine osteoarthritis (OA). In this study, we sought to extend these observations by investigating relationships between growth in early life, and clinical and radiological diagnoses of OA at the hand, knee and hip, among participants from the Hertfordshire Cohort Study. Data were available for 222 men and 222 women. Clinical OA was defined based on American College of Rheumatology criteria. Radiographs were taken of the knees and hips, and graded for the presence of osteophytes and overall Kellgren and Lawrence (KL) score. Lower weight at year one was associated with higher rates of clinical hand OA (OR 1.396, 95% CI 1.05, 1.85, P=0.021). Individuals with lower birth weights were more likely to have hip osteophytes (OR 1.512, 95% CI 1.14, 2.00, P=0.004) and this remained robust after adjustment for confounders. Furthermore, a low weight at one year was also associated with a higher osteophyte number in the lateral compartment of the knee, after adjustment for confounders (OR 1.388, 95% CI 1.01, 1.91, P=0.043). We have found further evidence of a relationship between early life factors and adult OA. These findings accord with previous studies.